Undergraduate teaching of gynecology. - Gonzáles del Riego, M. (2015)
Gynecology teaching in Pre-degree should in our view be aimed at training the general practitioner giving the expert knowledge that will be useful for a comprehensive treatment of patients. In our country, in which half of the female population is under 20 years and has very peculiar gynecological problems, specialized care in all cases is not feasible, what is required by the general practitioner is able to have knowledge suitable in gynecology and resolve some of these problems, referring complicated cases to specialists for a definitive diagnosis or treatment.